27+a=7(-4a+8)

Simple and best practice solution for 27+a=7(-4a+8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 27+a=7(-4a+8) equation:


Simplifying
27 + a = 7(-4a + 8)

Reorder the terms:
27 + a = 7(8 + -4a)
27 + a = (8 * 7 + -4a * 7)
27 + a = (56 + -28a)

Solving
27 + a = 56 + -28a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '28a' to each side of the equation.
27 + a + 28a = 56 + -28a + 28a

Combine like terms: a + 28a = 29a
27 + 29a = 56 + -28a + 28a

Combine like terms: -28a + 28a = 0
27 + 29a = 56 + 0
27 + 29a = 56

Add '-27' to each side of the equation.
27 + -27 + 29a = 56 + -27

Combine like terms: 27 + -27 = 0
0 + 29a = 56 + -27
29a = 56 + -27

Combine like terms: 56 + -27 = 29
29a = 29

Divide each side by '29'.
a = 1

Simplifying
a = 1

See similar equations:

| -8+3u=-20 | | 20a-13a-21=0 | | -5(2x-9)=2(x-7)-13 | | d(t)=1/3t-12 | | 19+2.50x=11+3.75x | | 3x-3=45-9x | | 9-3p=8p | | 3/2p-2=-7/9 | | 31-4r=-7(-4a+8) | | 3x^2+90=190-7x | | 2x+-5=12 | | 354=35t+.5*9.8*t^2 | | -24n^2=36n | | 2m^2+4=6m | | -2v-2v=-7(1+6r) | | 27=2m+5 | | Z^2+12Z-45=0 | | 20x6/14x2 | | 2m+37=67 | | 3-4x=-3x-2x | | -6.25=0.6x | | 2y+20=80 | | 5a+10b=45 | | -6x+18=-3(x-1) | | tan(x)=.48 | | 2(x-5)-3(2x+5)=5x+17 | | (8-i)(8+i)=0 | | 45t^2-72t+24=0 | | 3(8b+3)+6=36+3b | | 2(x-5)-3(2x+5)=5+17 | | 3p+5p=16 | | x+46=2x |

Equations solver categories